Does Investor Sentiment Drive Stock Market Bubbles? Beware of Excessive Optimism!. Issue 1 (2nd January 2020) - Pan, Wei-Fong
Abstract: The author examines the relationship between stock market bubbles and investor sentiment, as proxied by consumer confidence indices. The results indicate that investor sentiment significantly explains stock bubble probability and bubble expansion. Evidence suggests that investor sentiment positively affects the probability of stock bubble occurrences and bubble sizes. Evidence from impulse responses also suggests that investor sentiment positively reacts to bubble shocks. Further, the author observes that overly optimistic investor sentiment (a sentiment index that is too high) can be a useful predictor of a bubble burst. These findings are robust based on various model specifications.